Accessory cavitated uterine mass: an underdiagnosed condition and a diagnostic challenge - Yadav, Khushboo; Jaiswal, Deepshikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Accessory cavitated uterine mass (ACUM) is a rare Müllerian duct anomaly characterized by a non-communicating, cavitated lesion within the myometrium, lined by functional endometrium. ACUM often mimics other gynaecological disorders such as endometriosis, cystic adenomyoma, leiomyoma or cornual ectopic pregnancy, leading to diagnostic delays and significant morbidity. We present the case of a 28-year-old multiparous woman with a three-year history of severe, progressive dysmenorrhea and chronic pelvic pain refractory to standard medical management. Pelvic ultrasonography and MRI suggested possible endometriosis or chronic ectopic pregnancy. Definitive diagnosis achieved intraoperatively, a rudimentary horn–like, non-communicating cavity was identified, filled with fluid and surrounded by normal myometrium, consistent with ACUM. The patient underwent surgical resection of the accessory uterine cavity, resulting in complete resolution of her symptoms. This case underscores the importance of considering ACUM in the differential diagnosis of young nulliparous as well as multiparous women presenting with severe dysmenorrhea and chronic pelvic pain, especially when symptoms are refractory to initial treatment. Increased clinical awareness of ACUM’s characteristic features is essential to reduce diagnostic delay and improve patient outcomes.